Monarch of the glen. Series 2 [videorecording (DVD)] - Mackenzie, Compton, 1883-1972 (British Broadcasting Corp., 2004)
The second series of this heartwarming BBC hit features more humor, more beautiful scenery and more great moments with BBC stars Richard Briers and Susan Hampshire.